2017
DOI: 10.18203/2349-2902.isj20170191
|View full text |Cite
|
Sign up to set email alerts
|

Early and late outcomes of trans-abdominal pre-peritoneal and Lichtenstein repair for inguinal hernia, a comparative study

Mahmoud Abdel Latif Bahram

Abstract: Background: Surgical repair of inguinal hernia remains a common operation in general surgery. No consensus has been achieved on the best surgical technique of inguinal herniorrhaphy. Open repair has lower recurrence and complication rates. Laparoscopic approach has less postoperative pain, reduced recovery time, earlier return to activity and fewer wound complications but expose the patient to potential complications, mainly possibility of visceral injury. The aim was to compare early and late outcomes after T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…This result is similar to that found in other studies, where significantly lower consumption of these drugs was verified in the laparotomy technique 12 . Regarding chronic pain, the findings of this study are in line with current evidence, with a representation of more Lichtenstein patients complaining of pain, compared to TAPP 11 . However, the frequency of onset of pain, at the time of reassessment, was described as more frequent and more intense in those undergoing laparoscopic surgery.…”
Section: Chronic and Acute Postoperative Painsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is similar to that found in other studies, where significantly lower consumption of these drugs was verified in the laparotomy technique 12 . Regarding chronic pain, the findings of this study are in line with current evidence, with a representation of more Lichtenstein patients complaining of pain, compared to TAPP 11 . However, the frequency of onset of pain, at the time of reassessment, was described as more frequent and more intense in those undergoing laparoscopic surgery.…”
Section: Chronic and Acute Postoperative Painsupporting
confidence: 90%
“…According to current evidence, laparoscopic repair has a lower incidence of acute pain compared to open surgery. 1,11,12,13,14 In addition, patients submitted to laparoscopy reported a longer mean time of pain compared to the open technique, although 100% of these used analgesics, unlike those submitted to TAPP. This result is similar to that found in other studies, where significantly lower consumption of these drugs was verified in the laparotomy technique 12 .…”
Section: Chronic and Acute Postoperative Painmentioning
confidence: 99%
“…[11] In the study done by Bahram MAL et al the immediate and early postoperative pain was less in heavy weight mesh when compared to ours. [12] However, our study differs from the study done by Prakash et al in which there was no difference between heavyweight and lightweight mesh used for laparoscopic hernia repair at 24hrs postoperative period but the authors have not defined which scale was used for pain measurement. [13] There are several other studies with conflicting results.…”
Section: Discussionmentioning
confidence: 56%
“…Two studies conducted in 2016 by Latif Bahram [ 12 ] and Akhtar et al [ 24 ] compared laparoscopic and open hernia repair surgeries and concluded that laparoscopic surgery resulted in an early return to work for patients. Latif Bahram [ 12 ] compared 150 TAPP and 150 Lichtenstein repair (LR) cases and found that patients who underwent TAPP repair returned to work earlier than those who underwent LR. Similarly, Akhtar et al [ 24 ] conducted an RCT comprising 50 LR and 30 TAPP cases and concluded that patients who underwent TAPP repair returned to work earlier than those who underwent LR.…”
Section: Discussionmentioning
confidence: 99%
“…A significant difference in bilateral hernia repair favors laparoscopic over open hernia repair. In cases of recurrent hernia, postoperative recovery and long-term follow-up are better in laparoscopic surgery [2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%